EFFECT OF REGULATION OF SOURCE-SINK RELATIONSHIP ON SPIKE GROWTH RATE AND DRY MATTER ACUMUILATION FOR DIFFERENT WHEAT CULTIVARS - & Jaddoa, Kadom (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field trial was conducted at Abu-Ghraib Research Station-Agricultural Research Directorate-Ministry of Agriculture during the winter seasons of 2012-2013 and 2013-2014. The objective was to investigate the effect of source-sink Regulation on grain yield  and its companents of five bread wheat cultivars (Triticum aestivum L.( Randomized complete block design with the arrangement of split-plots with three replicates was used. Bread wheat cultivars (Bohooth-22, IPA 99, Abu-Ghraib-3,Al-Fath and Al-Rasheed) occupied the main plots while treatments of source-sink relationship modification occupied the sub-plots. They included eight treatments: Control (Con.), S1 (removal of lamina of the flag leaf of main stem), S2 (removal of laminas of the leaf  beneath the flag leaf), S3 (removal of both lamina of the leaf  and the leaf under flag leaf), S4 (removal of upper third spikelets),S5 (removal of median third spikelets), S6 (removal of lower third spikelets) and S7 (removal all spikelets from one side of spike)  . Characteristics spike growth rate (g), accumulated temperature (GDD), dry matter translocation All cultivars were significantly different in all studied characters in both seasons. Treatments of source-sink relationship regulation were significantly different in most studied characters in both seasons. Cultivar (Bohooth-22) gave higher spike growth rate (3.79 and 3.05 g), higher dry matter translocation (2.255 and 2.182 g) in both seasons, respectively, ) compared with Abu-Ghraib3 and Al-Rasheed cultivars which gave lowest as they possessed less spike growth rate (3.36 , 2.743, 3.65 and 2.687 g), less dry matter translocation (1.739, 1.829. 2.251 and 2.116 g) in both seasons, respectively. treatment (S5) in both seasons where the  median third of spikelets had been removed due to the reduction of spike growth rate (3.18 and 2.490 g) in both seasons compared with the (Con) treatment which gave the highest values of spike growth rate (3.915 and 3.129 g) in both seasons, respectively which resulted in the reduction of dry matter translocation in the (S5) treatment (1.50and 1.749 g) in both seasons, respectively.